2015
DOI: 10.1007/s10653-015-9725-9
|View full text |Cite
|
Sign up to set email alerts
|

The spatial relationship between human activities and C, N, P, S in soil based on landscape geochemical interpretation

Abstract: The development and formation of chemical elements in soil are affected not only by parent material, climate, biology, and topology factors, but also by human activities. As the main elements supporting life on earth system, the C, N, P, S cycles in soil have been altered by human activity through land-use change, agricultural intensification, and use of fossil fuels. The present study attempts to analyze whether and how a connection can be made between macroscopical control and microcosmic analysis, to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…The accumulation of heavy metals in peri-urban soils has high spatial variability and is affected by land-use type, surface structure, population and climatic conditions [20] . Many studies have found significant differences in heavy metal contents among diverse land-use types [21,22] . For example, Praveena SM et al found that land-use type is the main contributor to heavy metal exposure, and the soil heavy metal content in areas adjacent to roads was much higher than that in light industrial areas [23] .…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of heavy metals in peri-urban soils has high spatial variability and is affected by land-use type, surface structure, population and climatic conditions [20] . Many studies have found significant differences in heavy metal contents among diverse land-use types [21,22] . For example, Praveena SM et al found that land-use type is the main contributor to heavy metal exposure, and the soil heavy metal content in areas adjacent to roads was much higher than that in light industrial areas [23] .…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of heavy metals in peri-urban soils has high spatial variability and is affected by land-use type, surface structure, population and climatic conditions 23 . Many studies have found significant differences in heavy metal contents among diverse land-use types 24 , 25 . For example, Praveena et al found that land-use type is the main contributor to heavy metal exposure, and the soil heavy metal content in areas adjacent to roads was much higher than that in light industrial areas 26 .…”
Section: Introductionmentioning
confidence: 99%
“…A população do planeta deve atingir a marca de 11,2 bilhões de habitantes em 2100, com a preocupação não somente em se produzir alimentos, mas que ela seja realizada de maneira a garantir a sustentabilidade e a conservação ambiental (BONGAARTS, 2016). A agricultura é uma importante atividade econômica, onde muitas de suas práticas de manejo, como operações de preparo do solo, semeadura das culturas, aplicação de pesticidas e fertilizantes minerais, e monocultura têm impactado negativamente atributos físicos, químicos e bioquímicos do solo (LIMA et al;YU et al, 2016). Adicionalmente, alterações no uso e cobertura da terra proporcionam diretamente modificações na composição do habitat, na biodiversidade e no funcionamento do ecossistema, o que leva a alterações da qualidade ambiental (GARCÍA-MOZO; OTEROS; GALÁN, 2016).…”
Section: Introductionunclassified